How Multilingual Japanese Speakers Communicate With People in Bali - Indrowaty, Sri Aju; Faizah, Nurul; Setiawati, Eti; Lestari, Ida Puji; Yhustien, Dhea; Hasna, Oktavia (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. The purpose of this study is to describe how multilingual Balinese Japanese speakers interact with Bali residents. In this instance, being multilingual means being able to communicate in English, Indonesian, and one's mother tongue, which in this case is Japanese. The method employed is a descriptive qualitative approach using listening, recording, and recording techniques used between Japanese conversations that are in the Japanese community of Bali. The participants of this study are two couples of mixed marriages of Balinese and Japanese who live in Bali and have children. Methods are Code-switching, mingling, cooperative strategy, and nonlinguistic strategy which types of communication strategies are employed. The goal of this communication is to ensure that the conversation flows well and that the speaker realizes their objectives. This research is that in a society that is classified as multilingual, fluency and accuracy in conveying messages, or goals is something that must continue to be studied. This means that every language user when communicating verbally, not only conveys verbal messages but also needs to understand the function, context, topic, and situationKeywords: Multilingual; Communication strategy; Balinese; Japanese